2003
DOI: 10.1146/annurev.med.54.101601.152156
|View full text |Cite
|
Sign up to set email alerts
|

Calorie Restriction, Aging, and Cancer Prevention: Mechanisms of Action and Applicability to Humans

Abstract: Calorie restriction (CR) is the most effective and reproducible intervention for increasing lifespan in a variety of animal species, including mammals. CR is also the most potent, broadly acting cancer-prevention regimen in experimental carcinogenesis models. Translation of the knowledge gained from CR research to human chronic disease prevention and the promotion of healthy aging is critical, especially because obesity, which is an important risk factor for several chronic diseases, including many cancers, is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
388
2
6

Year Published

2004
2004
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 508 publications
(406 citation statements)
references
References 96 publications
10
388
2
6
Order By: Relevance
“…While being difficult to practice, this approach has a lot of scientific merit for being able to extend average life spans of many species of animals including rats, mice, fish, and possibly primates (currently being tested). Along with this life span extension is a reduction in chronic diseases that are common to mankind, reviewed in Hursting et al [6]. A recent meta-analysis of 14 experimental studies found that energy restriction resulted in a 55% reduction in spontaneous tumors in laboratory mice [7].…”
Section: Reviewmentioning
confidence: 99%
“…While being difficult to practice, this approach has a lot of scientific merit for being able to extend average life spans of many species of animals including rats, mice, fish, and possibly primates (currently being tested). Along with this life span extension is a reduction in chronic diseases that are common to mankind, reviewed in Hursting et al [6]. A recent meta-analysis of 14 experimental studies found that energy restriction resulted in a 55% reduction in spontaneous tumors in laboratory mice [7].…”
Section: Reviewmentioning
confidence: 99%
“…leads to the production of reactive oxygen species (ROS). ROS are involved in a variety of biological phenomena, such as mutation, carcinogenesis and aging (1,2). In the multistage carcinogenesis model, ROS are associated not only with initiation, but also with promotion and progression.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, tumor development and size is increased after subcutaneous injection of CRC cells in obese compared to non-obese mice (32). By contrast, animal studies have demonstrated that calorie restriction strongly inhibits cancer and slows tumor growth (33). In particular, calorie restriction inhibits spontaneous, transplanted, and carcinogen-induced colon cancer in mice and rats (34)(35)(36).…”
Section: Obesity and Colorectal Cancer Riskmentioning
confidence: 99%